Implementasi Pendekatan Sistematik Untuk Meningkatkan Kualitas Manajemen Pendidikan - Ardilla, Ovi; Syifa, Salsabila Mayla Nadhira; Sitompul, Abdul Lathif (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This article focuses on implementing a systematic approach to improve the quality of educational management. In this context, key elements of educational management, such as planning, organizing, control, and management system strategies, play a crucial role. This research aims to create a comprehensive model of educational management, where planning, organizing, controlling, and management strategies are integrated. In this design, the research adopts a Library Research approach. Implementing a systematic approach in educational management involves interconnected processes of planning, organizing, controlling, and evaluation to enhance educational quality effectively and sustainably. By conducting needs analysis, setting clear goals, coordinating programs, and utilizing methods like the Balanced Scorecard, educational institutions can manage resources efficiently, monitor performance, and adapt relevant strategies.